Selection of variables in mathematical models of culture parameters of marine shrimp Litopenaeus vannamei - Bezerra, Ady Marinho; Silva, José Antônio Aleixo da; Mendes, Paulo de Paula (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to select management variables of the marine shrimp Litopenaeus vannamei that most influenced culture variable responses (production, productivity, final weight and survival rate), in mathematical models. The database was composed of 83 cultures in the period of 2003 to 2005, obtained from a shrimp farm located in the South coast of Pernambuco. To estimate the parameters of the models it was used the technique of least square. The selection of variable was carried through the backward elimination process associated to the Box and Cox transformation. The adequacy of the equations and the hypothesis of normality and homogeneous variance for the errors were analyzed based on the analysis of variance and on the analysis of residuals. It is possible to correlate those variables and to establish predictions with the equations.